Hmboff/on as a switchable thiol protecting group for native chemical ligation. Issue 18 (22nd April 2016) - Qi, Yun-Kun; Tang, Shan; Huang, Yi-Chao; Pan, Man; Zheng, Ji-Shen; Liu, Lei
Abstract : A new thiol protecting group Hmb off/on is described, which has a switchable activity that may be useful in the chemical synthesis of complex proteins or peptides. Abstract : A new thiol protecting group Hmb off/on is described, which has a switchable activity that may be useful in the chemical synthesis of proteins. When placed on the side chain of Cys, Cys(Hmb off ) is stable to trifluoroacetic acid (TFA) in the process of solid-phase peptide synthesis. When Cys(Hmb off ) is treated with neutral aqueous buffers, it is cleanly converted to acid-labile Cys(Hmb on ), which can later be fully deprotected by TFA to generate free Cys. The utility of Cys(Hmb off/on ) is demonstrated by the chemical synthesis of an erythropoietin segment, EPO[Cys 98 –Arg 166 ]-OH through native chemical ligation.